The impact of two Ginseng administrations on stress from acute physical effort - Ramona-Niculina Jurcău; Dong Hun Kwak; Ioana-Marieta Jurcău; Nicolae-Alexandru Colceriu; Cezar Honceriu (Sport şi Societate)
Panax Ginseng (GSG) may be a useful agent for treating depression and anxiety. The aim of the research was to evaluate two administrations of a product containing GSG (P-GSG) in intense acute physical stress. Healthy men were voluntarily enrolled into 4 groups: control (C) no treatment; who received placebo (P); who received P-GSG for one week (GSG1); who received P-GSG for 3 weeks (GSG3). All participants were subjected to the same type of stress: an acute and short-term intense physical effort on a cycle ergometer. The administered products were: placebo and P-GSG. The scans were: anxiety (A) and heart rate (HR). Parameters were significantly increased at C and P, for A and HR compared to GSG1 and GSG3. The greatest impact of P-GSG was on A. GSG1 compared to GSG3 had a greater impact on A and HR. In conclusion, through this study we found that Panax Ginseng, especially if taken for a longer period of time, reduces heart rate and anxiety in short-term acute intense exercise stress.